EFFORTS TO IMPROVE READING SKILLS THROUGH LETTER CARD GAMES TO STUDENTS RA MUSTAFAWIYAH - Hamidah, Nur (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to describe the implementation of learning through letter card games for RA Al-Mustafawiyah students, to describe the improvement of reading skills, to describe the obstacles faced in the implementation of learning. The research method uses quantitative methods. Data collection techniques used learning implementation sheets, barriers sheets, and reading ability test results using letter card games. The results of this study indicate an assessment of n gain to assess students' reading ability, there are 15 students in the moderate category of 9 people and an increase in the high reading ability score of 6 people. It can be said that there is a significant increase in students' scores in the posttest scores. As for the obstacles that occur, namely, the lack of interest in reading students, students are less focused when learning takes place, many assignments pile up at home and some students are not taught by their parents because their parents work. All of these problems can be overcome by forming learning through letter card games.